Piezoelectric tools versus traditional oscillating saw for distal linear osteotomy in hallux valgus correction: Triple-blinded, randomized controlled study. Issue 3 (April 2022) - Mosca, Massimiliano; Russo, Alessandro; Caravelli, Silvio; Massimi, Simone; Vocale, Emanuele; Grassi, Alberto; Censoni, Davide; Fuiano, Mario; Zaffagnini, Stefano
Highlights: The mechanical conditions at the level of osteotomy significantly influence the biological process of bone healing. The advantages offered by piezoelectric surgery are represented by the absence of heat exposure and cut selectivity. The Authors showed to apply the principles of piezoelectric surgery in the orthopaedic field through a dedicated device. Abstract: Background: The main goal of the surgical correction of the hallux valgus is the morphological correction associated with the functional rebalancing of the first ray. The aim of this triple-blinded, randomized controlled study was to show the efficacy of piezosurgery in performing distal linear osteotomy of the first metatarsal bone in HV correction, in terms of clinical and radiological outcomes at 1-year final follow up. Methods and materials: This study was performed collecting prospectively pre-operative and post-operative data for all patients. 34 patients were included in the trial and were randomly allocated (1:1) in a Piezoelectric Group (PG) that involved the use of piezoelectric tools and in a Control Group (CG) that provided for the use of a traditional oscillating saw. In both groups, all patients were treated with a distal linear osteotomy of the first metatarsal bone. Clinical and radiographic assessments were performed. Results: The AOFAS score between the two groups was similar pre-operatively and during the follow-up period, with a slight superiority in the PG at each evaluation. The osteotomy surgical time was registered for both groups. Among the endpoints of the study, the radiological bone healing time was independently assessed by a radiologist that reported a lower mean value in the piezoelectric group compared with the control group. Conclusions: This trial has shown that piezoelectric surgery is not inferior to traditional methods from the clinical-functional point of view, but can even lead to an evident reduction of bone healing time with a statistical significance. Level of evidence: Level I.